NTS catecholamine neurons mediate hypoglycemic hunger via medial hypothalamic feeding pathways - Aklan, İltan; Sayar Atasoy, Nilufer; Yavuz, Yavuz; Ateş, Tayfun; Çoban, İlknur; Köksalar, Fulya; Filiz, Gizem; Topçu, İskalen Cansu; Öncül, Merve; Dilsiz, Pelin; Cebecioğlu, Utku; Alp, Muhammed İkbal; et al. (Cell Press, 2020)
Glucose is the essential energy source for the brain, whose deficit, triggered by energy deprivation or therapeutic agents, can be fatal. Increased appetite is the key behavioral defense against hypoglycemia; however, the central pathways involved are not well understood. Here, we describe a glucoprivic feeding pathway by tyrosine hydroxylase (TH)-expressing neurons from nucleus of solitary tract (NTS), which project densely to the hypothalamus and elicit feeding through bidirectional adrenergic modulation of agouti-related peptide (AgRP)- and proopiomelanocortin (POMC)-expressing neurons. Acute chemogenetic inhibition of arcuate nucleus (ARC)-projecting NTSTH neurons or their target, AgRP neurons, impaired glucoprivic feeding induced by 2-Deoxy-D-glucose (2DG) injection. Neuroanatomical tracing results suggested that ARC-projecting orexigenic NTSTH neurons are largely distinct from neighboring catecholamine neurons projecting to parabrachial nucleus (PBN) that promotes satiety. Collectively, we describe a circuit organization in which an ascending pathway from brainstem stimulates appetite through key hunger neurons in the hypothalamus in response to hypoglycemia.
Keywords: NTS; Catecholamine Neurons; Medial Hypothalamic